TMS 2020 149th Annual Meeting and Exhibition Supplemental proceedings (Springer, 2020)
This collection presents papers from the 149th Annual Meeting & Exhibition of The Minerals, Metals & Materials Society.
Includes indexes.
Keywords: Materials science -- Congresses.; Materials -- Technological innovations -- Congresses.; Materials -- Mathematical models -- Congresses.; elektronické knihy; electronic books